2023
DOI: 10.1021/acs.jpcc.3c04814
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation- and Vacancy-Enhanced Internal Electric Fields in ZnIn2S4 for Highly Efficient Photocatalytic H2O2 Production

Chong Ouyang,
Xinyao Quan,
Zi Ang Chen
et al.

Abstract: Defect engineering and intercalation modification are feasible strategies to enhance the internal electric field (IEF), which is an effective way for steering photogenerated charge kinetics. Herein, ethylene glycol (EG) and Zn vacancy (V Zn ) are successfully introduced into the intra-and interlayers of ZnIn 2 S 4 , respectively, based on the two-dimensional layered structure characteristic of ZnIn 2 S 4 and the special coordination effect between ethylene glycol and Zn 2+ . Comprehensive experimental analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(162 reference statements)
0
2
0
Order By: Relevance
“…Among these photocatalysts, CN has attracted much attention due to its high 2e – ORR selectivity, easy synthesis, low cost, suitable band structure, as well as excellent chemical stability. , However, the photocatalytic activity of CN to produce H 2 O 2 is low due to its limited light absorption and poor charge separation efficiency . To improve the photocatalytic activity of CN, various strategies have been proposed including the construction of heterojunctions, introduction of heteroatoms, defect engineering, and the enhancement of crystallinity. , Elemental doping provides a convenient approach to tune the optical, electronic, and other physical properties of CN and thus improves its photocatalytic performance . Various elements such as boron, potassium, and cobalt were doped in CN to achieve the enhanced photocatalytic activity. Teng et al investigated the effects of different metal dopants including Fe, Co, Ni, In, and Sn on the photocatalytic H 2 O 2 production performance of polymeric carbon nitride and found that In-doped CN showed the best photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these photocatalysts, CN has attracted much attention due to its high 2e – ORR selectivity, easy synthesis, low cost, suitable band structure, as well as excellent chemical stability. , However, the photocatalytic activity of CN to produce H 2 O 2 is low due to its limited light absorption and poor charge separation efficiency . To improve the photocatalytic activity of CN, various strategies have been proposed including the construction of heterojunctions, introduction of heteroatoms, defect engineering, and the enhancement of crystallinity. , Elemental doping provides a convenient approach to tune the optical, electronic, and other physical properties of CN and thus improves its photocatalytic performance . Various elements such as boron, potassium, and cobalt were doped in CN to achieve the enhanced photocatalytic activity. Teng et al investigated the effects of different metal dopants including Fe, Co, Ni, In, and Sn on the photocatalytic H 2 O 2 production performance of polymeric carbon nitride and found that In-doped CN showed the best photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…17 To improve the photocatalytic activity of CN, various strategies have been proposed including the construction of heterojunctions, introduction of heteroatoms, defect engineering, and the enhancement of crystallinity. 18,19 Elemental doping provides a convenient approach to tune the optical, electronic, and other physical properties of CN and thus improves its photocatalytic performance. 9 Various elements such as boron, potassium, and cobalt were doped in CN to achieve the enhanced photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%